Evaluation of confirmatory data following the Article 12 MRL review for bentazone. (22nd May 2019) - ,; Anastassiadou, Maria; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Lostia, Alfonso; Magrans, Jose Oriol; et al.
Abstract: The applicant BASF SE submitted a request to the competent national authority in the Netherlands to evaluate the confirmatory data that were identified for bentazone in the framework of the maximum residue level (MRL) review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, a new livestock feeding study and storage stability data for bentazone and 6‐hydroxy bentazone in animal matrices were submitted. To address the data gap for potatoes, adjusted less critical good agricultural practices (GAPs) were reported and supporting residue data were provided. The data gap related to analytical methods in fat and herbal infusions were addressed in the framework of the peer review. The data gap for residue trials on leek has not been addressed. Further confirmation from the applicant/Member States are needed for the clarification of the GAP for herbal infusions. Based on the information submitted in support of the confirmatory data request, the existing EU MRLs for bentazone need to be modified for potato and leek, for swine fat and kidney and for bovine, equine, goat and sheep fat, liver and milk. The consumer risk assessment performed in the MRL review was updated, using new toxicological reference values derived by the peer review. No consumer intake concerns were identified.